Characterization of Immunogenicity of Malignant Cells with Stemness in Intrahepatic Cholangiocarcinoma by Single-Cell RNA Sequencing - Jing Bian; Jianyang Fu; Xin Wang; Jihye Lee; Gagandeep Brar; Freddy E. Escorcia; Maggie Cam; Changqing Xie (Hindawi Limited, 2022)
Cancer stem cells (CSCs) are responsible for long-term maintenance of tumors and thought to play a role in treatment resistance. The interaction between stemness and immunogenicity of CSCs in the intrahepatic cholangiocarcinoma (iCCA) is largely unknown. Here, we used single-cell transcriptomic data to study immunogenicity of malignant cells in human iCCA. Using an established computerized method CytoTRACE, we found significant heterogeneity in stemness/differentiation states among malignant cells. We demonstrated that the high stemness malignant cells express much lower levels of major histocompatibility complex II molecules when compared to low stemness malignant cells, suggesting a role of immune evasion in high stemness malignant cells. In addition, high stemness malignant iCCA cells exhibited significant expression of certain cytokine members, including CCL2, CCL20, CXCL1, CXCL2, CXCL6, CXCL8, TNFRSF12A, and IL6ST, indicating communication with surrounding immune cells. These results indicate that high stemness malignant cells retain their intrinsic immunological feature that facilitate the escape of immune surveillance.